Advances And Emerging Trends In Medical Device Technology: A Comprehensive Review (The Review of Diabetic Studies, 2025)
BackgroundMedical device technology has evolved from rudimentary tools to sophisticated systems integrating AI, IoMT, nanotechnology, and robotics, revolutionizing diagnosis, treatment, and monitoring across clinical domains.​MethodsThis comprehensive review synthesizes recent literature on advances in device categories (diagnostic, therapeutic, monitoring, implantable), emerging technologies, regulatory frameworks, clinical impacts, challenges, and future directions through historical analysis, classification overviews, and case studies from regulatory databases and clinical trials.​ResultsKey findings highlight innovations like AI-enhanced imaging, wearable biosensors, 3D-printed implants, and precision therapies improving outcomes in cardiology, oncology, and neurology, alongside challenges in biocompatibility, cybersecurity, and global accessibility.​ConclusionsEmerging trends promise personalized, predictive healthcare via integrated technologies, necessitating enhanced regulatory harmonization, cross-disciplinary collaboration, and equitable access to maximize clinical benefits and safety.​